2003
DOI: 10.1071/sr02038
|View full text |Cite
|
Sign up to set email alerts
|

Subsoil nitrogen mineralisation and its potential to contribute to NH4 accumulation in a Vertosol

Abstract: High concentrations of NH 4 + (up to 270 kg N/ha) have been observed in a Vertosol below 1 m depth in south-east Queensland. This study examined the possibility that mineralisation associated with the removal of native vegetation (Acacia harpophylla) for cropping was responsible for the production of NH 4 + . Particularly, the potential contribution of decomposing root material and/or dissolved organic nitrogen (DON) leached into the subsoil after clearing was investigated. The amount of N that was contained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Wider C:N ratio in the subsoil layers in wooded than in cropland fields may be due to high level of SOC attributed to deep root system of native perennials. Page et al (2003) reported that removal of deep-rooted native vegetation (Acacia harpophylla Benth.) and introducing shallow-rooted crops changed the soil environment, lowered SOC, and contributed to subsoil NH 4 concentration.…”
Section: Soil Nitrogen Concentration and C:n Ratiomentioning
confidence: 99%
“…Wider C:N ratio in the subsoil layers in wooded than in cropland fields may be due to high level of SOC attributed to deep root system of native perennials. Page et al (2003) reported that removal of deep-rooted native vegetation (Acacia harpophylla Benth.) and introducing shallow-rooted crops changed the soil environment, lowered SOC, and contributed to subsoil NH 4 concentration.…”
Section: Soil Nitrogen Concentration and C:n Ratiomentioning
confidence: 99%
“…Jones and Hodge (1999) reported that 10% of amino acids were adsorbed to the solid phase. Page et al (2003) showed that net N mineralization was not detected in the subsoil (2.7-3 m) of a Vertisol amended with a source of organic N. The nitrification rate in the subsoil of the Vertisol was extremely low due to lacking of an active nitrifying population in deep soil layers (Page et al, 2002). They believed that the microbial population of the subsoil had lower capacity for N mineralization than surface soil organisms.…”
Section: Nitrogen Mineralization and Nitrificationmentioning
confidence: 99%
“…Since this study has clearly failed to identify the source of the subsoil NH 4 + at the Warra site, further hypotheses regarding the mechanism of NH 4 + formation need to be identified. As discussed previously, it is already known that mineralisation (Page et al 2003) and fixed NH 4 + release (K. Page, unpublished data) are not capable of significantly contributing to exchangeable NH 4 + concentrations. However, it is known that NO 3 will readily leach through Vertosol soils such as Warra (Waring and Saffigna 1984;Catchpoole 1992;Ridge et al 1996), and the possibility that any NO 3 leached could be reduced to NH 4 + is another pathway yet to be investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Total carbon and nitrogen were analysed using a LECO CNS 2000 combustion analyser. A more detailed description of the Warra soil down to 3 m is given in Page et al (2002Page et al ( , 2003.…”
Section: Soil Sampling and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation